Rhinovirus Infection Induces Degradation of Antimicrobial Peptides and Secondary Bacterial Infection in Chronic Obstructive Pulmonary Disease - Mallia, Patrick; Footitt, Joseph; Sotero, Rosa; Jepson, Annette; Contoli, Marco; Trujillo-Torralbo, Maria-Belen; Kebadze, Tatiana; Aniscenko, Julia; Oleszkiewicz, Gregory; Gray, Katrina; Message, Simon D.; Ito, Kazuhiro; et al. (American journal of respiratory and critical care medicine, 2012)
Chronic obstructive pulmonary disease (COPD) exacerbations are associated with virus (mostly rhinovirus) and bacterial infections, but it is not known whether rhinovirus infections precipitate secondary bacterial infections. To investigate relationships between rhinovirus infection and bacterial infection and the role of antimicrobial peptides in COPD exacerbations. We infected subjects with moderate COPD and smokers and nonsmokers with normal lung function with rhinovirus. Induced sputum was collected before and repeatedly after rhinovirus infection and virus and bacterial loads measured with quantitative polymerase chain reaction and culture. The antimicrobial peptides secretory leukoprotease inhibitor (SLPI), elafin, pentraxin, LL-37, α-defensins and β-defensin-2, and the protease neutrophil elastase were measured in sputum supernatants. After rhinovirus infection, secondary bacterial infection was detected in 60% of subjects with COPD, 9.5% of smokers, and 10% of nonsmokers (P < 0.001). Sputum virus load peaked on Days 5-9 and bacterial load on Day 15. Sputum neutrophil elastase was significantly increased and SLPI and elafin significantly reduced after rhinovirus infection exclusively in subjects with COPD with secondary bacterial infections, and SLPI and elafin levels correlated inversely with bacterial load. Rhinovirus infections are frequently followed by secondary bacterial infections in COPD and cleavage of the antimicrobial peptides SLPI and elafin by virus-induced neutrophil elastase may precipitate these secondary bacterial infections. Therapy targeting neutrophil elastase or enhancing innate immunity may be useful novel therapies for prevention of secondary bacterial infections in virus-induced COPD exacerbations.